Functional genomics analysis identifies loss of HNF1B function as a cause of Mayer–Rokitansky–Küster–Hauser syndrome. Issue 6 (25th October 2022) - Thomson, Ella; Tran, Minh; Robevska, Gorjana; Ayers, Katie; van der Bergen, Jocelyn; Gopalakrishnan Bhaskaran, Prarthna; Haan, Eric; Cereghini, Silvia; Vash-Margita, Alla; Margetts, Miranda; Hensley, Alison; Nguyen, Quan; et al.
Abstract: Mayer–Rokitansky–Küster–Hauser (MRKH) syndrome is a congenital condition characterized by aplasia or hypoplasia of the uterus and vagina in women with a 46, XX karyotype. This condition can occur as type I when isolated or as type II when associated with extragenital anomalies including kidney and skeletal abnormalities. The genetic basis of MRKH syndrome remains unexplained and several candidate genes have been proposed to play a role in its etiology, including HNF1B, LHX1 and WNT4 . Here, we conducted a microarray analysis of 13 women affected by MRKH syndrome, resulting in the identification of chromosomal changes, including the deletion at 17q12, which contains both HNF1B and LHX1 . We focused on HNF1B for further investigation due to its known association with, but unknown etiological role in, MRKH syndrome. We ablated Hnf1b specifically in the epithelium of the Müllerian ducts in mice and found that this caused hypoplastic development of the uterus, as well as kidney anomalies, closely mirroring the MRKH type II phenotype. Using single-cell RNA sequencing of uterine tissue in the Hnf1b -ablated embryos, we analyzed the molecules and pathways downstream of Hnf1b, revealing a dysregulation of processes associated with cell proliferation, migration and differentiation. Thus, we establish that loss of Hnf1b function leads to an MRKH phenotype and generate the first mouse model of MRKH syndrome type II. Our results support the investigation of HNF1B in clinical genetic settings of MRKH syndrome and shed new light on the molecular mechanisms underlying this poorly understood condition in women's reproductive health.